Determining Talent Based on Student Skills Using Fuzzy Logic - Gusti Rahmadani (International Journal of Health Engineering and Technology, 2022)
Education is a conscious, planned effort to create a learning atmosphere and the learning process of students actively develops their potential to have spiritual, religious, self-control, personality, intelligence, noble character, and skills needed by themselves, society, nation and state. Learning is generally defined as a change in an individual that occurs through experience, and not because of the growth or development of his body or characteristics of a person since birth. So that they understand and know the best things to do to develop their knowledge, potential, and talents and skills. Because these talents are relatively stable, they can be used to help success in education and careers. Thus it can be said that talent reveals the potential to learn a certain activity, talent is relatively different, talent is relatively constant. Fuzzy logic is a logic that has a value of fuzzyness between true or false (Professor Lotfi A, 1965). Fuzzy logic is generally in problems that contain uncertainty (uncertainty), imprecision (inaccuracy), noise, and so on. Education is a conscious, planned effort to create a learning atmosphere and the learning process of students actively develops their potential to have spiritual, religious, self-control, personality, intelligence, noble character, and skills needed by themselves, society, nation and state. Learning is generally defined as a change in an individual that occurs through experience, and not because of the growth or development of his body or characteristics of a person since birth. So that they understand and know the best things to do to develop their knowledge, potential, and talents and skills. Because these talents are relatively stable, they can be used to help success in education and careers. Thus it can be said that talent reveals the potential to learn a certain activity, talent is relatively different, talent is relatively constant. Fuzzy logic is a logic that has a value of fuzzyness between true or false (Professor Lotfi A, 1965). Fuzzy logic is generally in problems that contain uncertainty (uncertainty), imprecision (inaccuracy), noise, and so on.